Signs, curls, and time variations: learning to appreciate Faraday’s law - Sihvola, A.; Leppävirta, J.; Kettunen, H. (Advanced Electromagnetics, 2012)
In this article, we present the analysis of a study on the development of conceptual understanding of dynamic electromagnetic fields of electrical engineering students in Finland. The focus of the study was teaching and understanding of Faraday’s law. A coil with two light-emitting diodes and a strong permanent magnet were used with which the induced electromotive force could be made visible. However, the field and flux directions, temporal changes, and topological constellations within this setting determine in a subtle manner the character of the resulting electric effect. The demonstration was used on electromagnetic field theory classes at Aalto University, Finland, to assess the conceptual understanding of the students. Drawing from the Peer Instruction principle, the students were asked to fill in a questionnaire concerning this experiment, first on their own, and once again after discussing with their neighbors in the classroom. They were asked about the direction of the electric force and the confidence of their answer. The results show that the answer is not very obvious: students tend to vote for the wrong answer. The Peer Instruction discussion greatly improves the situation. Also, the confidence of the students increases thanks to the discussion period with neighbors. The results, however, seem to be somewhat sensitive to the exact constellation and the administration of the experiment.